Research: Further Deepening the “Teaching” and “Learning” Approaches in Music Curriculum Units - Nan, Jiang (Journal of Research in Vocational Education, 2025)
This study focuses on the further deepening “teaching” and “learning” approaches in music curriculum units. It explores four dimensions—emotion, structure, integration, and individuality—by implementing immersive empathy-integrated education grounded in emotion; constructing unit frameworks based on student profiles and curriculum standards; achieving vertical integration through secondary creation of musical works and horizontal integration via interdisciplinary collaboration; and fostering personalized growth by excavating cultural connotations of works and creating experiential scenarios for creative adaptations. The study provides strategic references for innovation in music education, aiming to enhance students’ musical literacy and comprehensive competencies.